Evaluation of cheiloplasty and palatoplasty on palate surface area in children with oral clefts: longitudinal study. Issue 4 (May 2022) - Prado, Danielle Zola Almeida; Ambrosio, Eloá Cristina Passucci; Jorge, Paula Karine; Sforza, Chiarella; De Menezes, Márcio; Soares, Simone; Carrara, Cleide Felício Carvalho; Valarelli, Fabrício Pinelli; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract: This study evaluated the palatal surface area in children with different oral clefts after primary surgeries and at five years of age. This longitudinal study was composed by 216 digital models: unilateral complete cleft lip (UCL), unilateral complete cleft lip and palate (UCLP), and complete cleft palate (CP). The models were analysed at four time periods: T1 (before cheiloplasty), T2 (before palatoplasty), T3 (after palatoplasty); and T4 – (at five years of age). Area of the dental arches was measured through stereophotogrammetry software. Measurements evaluated with Student's test and ANOVA followed by the Tukey test (p<0.05) (AQ 1). In the UCL group, the palatal surface area significantly increased among phases. In the primary surgery periods, UCLP and CP significantly decreased (p<0.001). Palatal area in the UCLP group was significantly greater than the CP group. Overall, no statistically significant differences occurred among groups. At T4, the area of the palate in the UCL group was significantly greater than the UCLP group and no significant differences occurred between UCLP and CP groups. This study suggests that cheiloplasty did not inhibit the growth of the palatal surface area in children with UCL and UCLP. Palatoplasty significantly decreased the palatal area in children with UCLP and CP, demonstrating a significant negative effect of palatal repair on maxillary growth. At five years, children with UCLP and CP had a significantly smaller palate area than those with UCL.